Essays on financial risk modelling : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Finance, School of Economics and Finance, Massey University, Auckland, New Zealand - Nguyen, Thao Thac Thanh (Massey University, 2024)
In today’s highly interconnected financial landscape, the risk of shock spillover is a critical factor contributing to increased systemic risk and impacting the global financial stability. Research on spillover effects has gained significant attention from both academics and practitioners. This thesis aims to contribute to this strand of the literature by conducting three studies that employ a variety of connectedness methods to investigate several underexplored issues within the field of financial risk management. These essays delve further into the evolution of these spillover effects during times of extreme financial uncertainty and aim to identify the key drivers of these spillovers. Essay One investigates the high-frequency spillover of volatility shocks across major oil-dependent foreign exchange markets, considering the impact of the oil market’s volatility regime. Essay Two examines the return shock spillover between European sectoral credit default swap and the natural gas markets. This investigation is conducted across different quantiles of return distributions, with a special focus on understanding the effects of the ongoing Russian-Ukrainian war on this spillover. Essay Three scrutinizes spillover effects of inflation shocks under normal economic conditions and extreme inflationary conditions between the U.S. and emerging markets. The essay further unveils the determinants of the inflation spillovers among the sample markets.
Keywords: Financial risk management; International finance; Mathematical models; Swaps (Finance); Inflation (Finance); spillover; financial interconnectedness; quantile connectedness; risk modelling; 350207 International finance